2000
DOI: 10.1086/308733
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of the Effective Equation of State of the Intergalactic Medium

Abstract: We develop a method to extract the "effective equation of state" of the intergalactic medium from the Doppler (b) parameter distribution of the low-density Lyα forest. We test the method on numerical simulations and then apply it to published observations of the Lyα forest at redshifts z ≃ 0 to 4. We find that the effective equation of state is close to isothermal at redshift z ∼ 3, indicating that a second reheating of the IGM took place at z ∼ 3. This reheating can plausibly be identified with the reionizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
364
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 261 publications
(401 citation statements)
references
References 39 publications
36
364
1
Order By: Relevance
“…Combining the observations with the numerical simulations, Schaye et al (2000) found that b c at the fixed overdensity δ = 0, b δ=0 , increases from z ∼ 4.5 (b δ=0 ∼ 14.5 km s −1 ) to z ∼ 3 (b δ=0 ∼ 19.5 km s −1 ) due to He ii reionization at z ∼ 3 and then decreases from z ∼ 3 (b δ=0 ∼ 19.5 km s −1 ) to z ∼ 1.8 (b δ=0 ∼ 14 km s −1 ). Ricotti et al (2000) also found a similar increase in b δ=0 at z ∼ 3, although their b δ=0 at z > 2.8 and at z < 2.8 can be considered to be constant at b δ=0 ∼ 14.5 km s −1 and at b δ=0 ∼ 21 km s −1 , respectively. On the other hand, adopting a slightly different approach for identifying absorption lines instead of the Voigt profile fitting, McDonald et al (2000) found that there is no b c evolution over 2.1 < z < 4.4 at the slightly higher overdensity δ = 0.4.…”
Section: The Z-evolution Of B C (N H I )mentioning
confidence: 56%
See 1 more Smart Citation
“…Combining the observations with the numerical simulations, Schaye et al (2000) found that b c at the fixed overdensity δ = 0, b δ=0 , increases from z ∼ 4.5 (b δ=0 ∼ 14.5 km s −1 ) to z ∼ 3 (b δ=0 ∼ 19.5 km s −1 ) due to He ii reionization at z ∼ 3 and then decreases from z ∼ 3 (b δ=0 ∼ 19.5 km s −1 ) to z ∼ 1.8 (b δ=0 ∼ 14 km s −1 ). Ricotti et al (2000) also found a similar increase in b δ=0 at z ∼ 3, although their b δ=0 at z > 2.8 and at z < 2.8 can be considered to be constant at b δ=0 ∼ 14.5 km s −1 and at b δ=0 ∼ 21 km s −1 , respectively. On the other hand, adopting a slightly different approach for identifying absorption lines instead of the Voigt profile fitting, McDonald et al (2000) found that there is no b c evolution over 2.1 < z < 4.4 at the slightly higher overdensity δ = 0.4.…”
Section: The Z-evolution Of B C (N H I )mentioning
confidence: 56%
“…The cutoff slope (Γ T −1) is proportional to (γ T − 1). This cutoff envelope provides a probe of the gas temperature of the IGM at a given z, thus giving a powerful constraint on the thermal history of the IGM Lu et al 1996;Kirkman & Tytler 1997;Zhang et al 1997;Schaye et al 1999;McDonald et al 2000;Ricotti et al 2000;Schaye et al 2000). In practice, defining b c (N H i ) in an objective manner is not trivial due to the finite number of available absorption lines, sightline-to-sightline cosmic variances, limited S/N , and unidentified metal lines.…”
Section: The Lower Cutoff B Parametermentioning
confidence: 99%
“…(1)), which is thought to arise from the competition between photoheating and cooling due to the adiabatic expansion of the Universe, following reionization. The evolution of this relation has been measured in the data and depends on the reionization history and the hardness of the UV background (Schaye et al 2000;Ricotti et al 2000;Rollinde et al 2013), although in reality the picture is more complicated -because of radiative transfer effects during the epoch of HeII reionization. Nevertheless, the temperature at the characteristic overdensity probed by the Lyα is now quite well measured (e.g.…”
Section: Visualizationsmentioning
confidence: 99%
“…Another difficulty is that observations of the Lya forest indicate a much lower temperature for the majority of the intergalactic medium at (Bryan z ∼ 2-3 1 Hubble Fellow. & Machacek 2000; Schaye et al 1999), a condition that may extend to even lower redshifts (Ricotti, Gnedin, & Shull 2000). Although hardly conclusive, these concerns may be pointing toward another explanation for the observations.…”
Section: Introductionmentioning
confidence: 95%